TÜRKİYE'DE YETİŞEN BAZI CİRSİUM MİLLER TÜRLERİNDE KARYOLOJİK BİR ARAŞTIRMA - KAYA, TUBAY (Fırat Üniveristesi, 2009)
Bu araştırmada, Türkiye genelinde yayılış gösteren Cirsium Miller cinsine ait yedi takson C. caucasicum (Adams) Petrak, C. kosmelii (Adams) Fisch. Ex Hohen, C. leuconeorum Boiss. & Hausskn, C. cassium Davis & Paris, C. agregatum Ledeb., C. echinus (Bieb.) Haand.-Mazz., C. rhizocephalum C.A. Meyer subsp, sinuatum (Boiss). Davis & Parris, karyolojik bakımdan incelenmiştir. İncelenen yedi taksonun (C. caucasicum, C. kosmelii, C. leuconeorum, C. cassium, C. agregatum, C. echinus, C. rhizocephalum) kromozom incelemeleri için tohumlarından yararlanılmıştır. Kromozom çalışmaları sonucunda türlerin somatik kromozomlarının sayım ve ölçümleri yapılmıştır. Kromozom sayıları C. cassium da 2n=36 ve diğer türlerde 2n= 34 olarak bulunmuştur. Bütün kromozomlar median noktalı (M), median bölgeli (m) ve submedian (sm) sentromerli bulunmuştur.

In this research, Seven taxa belong to genus Cirsium Miller in growing Turkey (C. caucasicum (Adams) Petrak, C. kosmelii (Adams) Fisch. Ex Hohen, C. leuconeorum Boiss. & Hausskn, C. cassium Davis & Paris, C. agregatum Ledeb., C. echinus (Bieb.) Haand.-Mazz., C. rhizocephalum C.A. Meyer subsp, sinuatum (Boiss). Davis & Parris) were investigated in point of karyologic. The seeds of investegated seven spesies (C. caucasicum, C. kosmelii, C. leuconeorum, C. cassium, C. agregatum, C. echinus, C. rhizocephalum) were used for chromosomes analysis. The numbers and measurements of somatic chromosomes were carried in results of chromosomes works. In this species, the chromosome numbers were in C. cassium 2n=36 and 2n= 34 in other species. All of the chromosomes had median point (M), median region (m), or submedian (sm) centromeres.
A karyologic investigation at some Cirsium species growing in Turkey
Keywords: Biyoloji